DIGITAL DYNAMIC MARKETING CAPABILITY FOR GREEN HOSPITALITY TRANSFORMATION IN EMERGING COUNTRIES : A SYSTEMATIC LITERATURE REVIEW AND EMPIRICAL TREND ANALISYS - Sianipar, Ardin; Angelia, Widya; Abdau, Abrar (DeReMa (Development Research of Management): Jurnal Manajemen, 2025)
This study explores the role of Digital Dynamic Marketing Capability (DDMC) in advancing green hospitality in emerging countries by integrating theoretical and empirical insights. A Systematic Literature Review (SLR) following the PRISMA protocol analyzed 30 peer-reviewed articles from 2020 to 2024, sourced from Scopus and Web of Science, and supplemented by empirical data from WTTC, UNWTO, and Statista to validate trends. The findings highlight four key themes: technological adaptability, sustainability-driven digital communication, organizational agility, and customer eco-engagement. DDMC strengthens branding, fosters eco-innovation, and enhances service personalization, though its adoption, particularly of advanced technologies like AI and blockchain, varies across regions due to infrastructural and resource disparities. The study’s reliance on secondary data limits its ability to establish direct causal relationships, suggesting a need for further empirical research. Practically, it offers strategic insights for hospitality leaders and policymakers to develop adaptive, sustainable marketing practices that align with eco-hospitality goals. By extending dynamic capabilities theory to green digital marketing, this paper contributes an original conceptual framework tailored to the unique challenges and opportunities of emerging markets, providing a roadmap for sustainable transformation in the hospitality sector. Abstrak dalam Bahasa Indonesia : Studi ini mengeksplorasi peran Digital Dynamic Marketing Capability (DDMC) dalam memajukan green hospitality di negara berkembang melalui integrasi wawasan teoretis dan empiris. Systematic Literature Review (SLR) dengan protokol PRISMA menganalisis 30 artikel peer-reviewed periode 2020–2024 yang bersumber dari Scopus dan Web of Science, serta dilengkapi dengan data empiris dari WTTC, UNWTO, dan Statista untuk memvalidasi tren. Temuan penelitian menyoroti empat tema utama: kemampuan beradaptasi terhadap teknologi, komunikasi digital berorientasi keberlanjutan, kelincahan organisasi, dan keterlibatan pelanggan dalam isu lingkungan. DDMC memperkuat branding, mendorong inovasi ramah lingkungan (eco-innovation), dan meningkatkan personalisasi layanan, meskipun adopsinya—terutama pada teknologi maju seperti AI dan blockchain—bervariasi antar wilayah akibat perbedaan infrastruktur dan sumber daya. Ketergantungan studi ini pada data sekunder membatasi kemampuannya dalam menetapkan hubungan kausal langsung, sehingga diperlukan penelitian empiris lanjutan. Secara praktis, studi ini memberikan wawasan strategis bagi para pemimpin industri perhotelan dan pembuat kebijakan untuk mengembangkan praktik pemasaran adaptif dan berkelanjutan yang selaras dengan tujuan eco-hospitality. Dengan memperluas teori dynamic capabilities ke dalam pemasaran digital berkelanjutan, penelitian ini menawarkan kerangka konseptual orisinal yang disesuaikan dengan tantangan dan peluang unik di pasar negara berkembang, sekaligus memberikan peta jalan bagi transformasi berkelanjutan di sektor perhotelan.